Integration of Islamic Values in Local Wisdom to Realize Tolerance (Religious Moderation Village) in Gunung Malang Village Sumberjambe Jember - Heridianto, Heridianto; Sholihah, Imro’atus; Asfiyah, Wardatul (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2026)
This research aims to analyze the integration of Islamic values and local wisdom in shaping the practice of tolerance between religions at the family and community levels. Studies of religious moderation in Indonesia have so far emphasized the role of the state and formal institutions, while the practice of tolerance that grows naturally in the family and local culture is still relatively understudied. This research is located in Gunung Malang Village, Sumberjambe District, Jember Regency, a multicultural village known for having a harmonious social life without open religious conflicts. The research uses a qualitative approach with a case study design. The data was collected through in-depth interviews with 12 informants consisting of religious leaders, traditional leaders, village officials, and interfaith families. Participatory observation was carried out for four months to capture the daily social practices of the community. Data analysis was carried out thematically using the help of NVivo 12 software until it reached the data saturation point. The results of the study show that there are three main patterns of tolerance, namely: (1) Negotiation of religious values in interfaith families, (2) Interfaith social participation in life cycle events such as marriage and death, and (3) Social solidarity based on mutual cooperation. This pattern reflects the integration of Islamic values such as rahmah, justice and ukhuwah insaniyah with local wisdom in the form of kinship systems and village deliberations. This research contributes to formulating a model of tolerance based on family and local culture as a contextual and sustainable form of religious moderation.